Engineering Responses to Climate Change: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2022)
At the forum held during the 2021 annual meeting of the National Academy of Engineering, distinguished engineers gathered virtually to explore the roles that engineers can play in both mitigating and helping society adapt to climate change. Through a series of brief presentations and responses to questions from the moderator and the forum audience, the speakers discussed many of the issues at the forefront of climate-related engineering practice and policy today. This publication highlights the presentation and discussion of the event.

The Climate Change Educational Partnership: Climate Change, Engineered Systems, and Society: A Report of Three Workshops - National Academy of Engineering (The National Academies Press, 2014)
Societies develop engineered systems to address or mediate climate-related problems, such as drought, sea-level rise or wildfire control; the mediation involves public trust, public engagement, and governance. In these efforts, societies also decide - intentionally or implicitly - questions of justice and sustainability, such as what areas will receive mediation measures, what types of measures will be used, and what levels and kinds of local impacts are tolerated. In September 2010, the Center for Engineering, Ethics, and Society at the National Academy of Engineering began working with four other partners on a Climate Change Educational Partnership Phase I planning grant from the National Science Foundation. The project focused on defining and characterizing the societal and pedagogical challenges posed by the interactions of climate change, engineered systems and society, and identifying the educational efforts that a network could use to enable engineers, teachers, students, policymakers, and the public to meet the challenges. The project also aimed to build awareness of the complexities among a diverse set of communities affected by climate change and engineered systems and to engage the communities in addressing these challenges. The Climate Change Educational Partnership is the summary of three workshops convened over the course of the grant on the interactions of climate change with engineered systems in society and the educational efforts needed to address them. The first workshop provided the partners with an introduction to the varied social and technical dimensions found in the relationships among climate, engineered systems, and society. The second workshop built on the common language developed in the first. It allowed the partners to expand involvement in the project to include representatives from community and tribal colleges, professional societies and business. It examined the opportunities and challenges for formal and informal education, particularly in engineering classrooms and science museums, to prepare students and citizens to address these issues. The third workshop allowed the partners to broaden further the discussion and the audience. It solicited participation from government officials, Native American tribal representatives, professional society leaders, as well as educators, artists, scientists, and engineers who are developing programs that can manage change and educate students and citizens in ways that foster their leadership skills. The Climate Change Educational Partnership will be a useful resource to engineers, educators, corporate leaders, local and regional officials, members of professional societies, and others in their efforts to understand and address the challenges of climate change and its societal impacts.

Adapting Agricultural Extension to Peacebuilding: Report of a Workshop by the National Academy of Engineering and United States Institute of Peace: Roundtable on Technology, Science, and Peacebuilding - National Academy of Engineering (The National Academies Press, 2012)
Societies have sought to improve the outputs of their agricultural producers for thousands of years. In the 19th and early 20th centuries, efforts to convey agricultural knowledge to farmers became known as extension services, a term adopted from programs at Oxford and Cambridge designed to extend the knowledge generated at universities to surrounding communities. Traditionally, extension services have emphasized a top-down model of technology transfer that encourages and teaches producers to use crop and livestock varieties and agricultural practices that will increase food production. More recently, extension services have moved toward a facilitation model, in which extension agents work with producers to identify their needs and the best sources of expertise to help meet those needs. On May 1, 2012, the Roundtable on Science, Technology, and Peacebuilding held a workshop in Washington, DC, to explore whether and how extension activities could serve peacebuilding purposes. The Roundtable is a partnership between the National Academy of Engineering (NAE) and the U.S. Institute of Peace (USIP). It consists of senior executives and experts from leading governmental organizations, universities, corporations, and nongovernmental organizations, was established in 2011 to make a measurable and positive impact on conflict management, peacebuilding, and security capabilities. Its principal goals are: To accelerate the application of science and technology to the process of peacebuilding and stabilization; To promote systematic, high-level communication between peacebuilding and technical organizations on the problems faced and the technical capabilities required for successful peacebuilding; and To collaborate in applying new science and technology to the most pressing challenges for local and international peacebuilders working in conflict zones.

Privacy and Security in the 21st Century: Who Knows and Who Controls?: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2019)
New technologies and capabilities, such as Google Cloud and artificial intelligence, are changing the world at an unprecedented rate. A transition to cloud computing offers a variety of benefits, including worldwide access and faster networks. This digital transformation also presents an array of new challenges. The privacy and security of these systems is one of the most discussed subjects of the current century. The theme of the National Academy of Engineering Annual Meeting on September 30th and October 1st, 2018 was privacy and security in the 21st century. Topics of discussion included new security regulations and procedures to mitigate the new range of threats that this era presents. Understanding privacy in new digital contexts and building security into systems with the use of artificial intelligence are necessary steps in order to protect our data in the future. This publication summarizes the presentations and discussions from the forum.

Engineering Societies and Undergraduate Engineering Education: Proceedings of a Workshop - National Academy of Engineering (The National Academies Press, 2017)
Engineering professional societies in the United States are engaged in a wide range of activities involving undergraduate education. However, these activities generally are not coordinated and have not been assessed in such a way that information about their procedures and outcomes can be shared. Nor have they been assessed to determine whether they are optimally configured to mesh with corresponding initiatives undertaken by industry and academia. Engineering societies work largely independently on undergraduate education, leaving open the question of how much more effective their efforts could be if they worked more collaboratively2014with each other as well as with academia and industry. To explore the potential for enhancing societies' role at the undergraduate level, the National Academy of Engineering held a workshop on the engagement of engineering societies in undergraduate engineering education. This publication summarizes the presentations and discussions from the workshop.

Making Value: Integrating Manufacturing, Design, and Innovation to Thrive in the Changing Global Economy: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2012)
Manufacturing is in a period of dramatic transformation. But in the United States, public and political dialogue is simplistically focused almost entirely on the movement of certain manufacturing jobs overseas to low-wage countries. The true picture is much more complicated, and also more positive, than this dialogue implies. After years of despair, many observers of US manufacturing are now more optimistic. A recent uptick in manufacturing employment and output in the United States is one factor they cite, but the main reasons for optimism are much more fundamental. Manufacturing is changing in ways that may favor American ingenuity. Rapidly advancing technologies in areas such as biomanufacturing, robotics, smart sensors, cloud-based computing, and nanotechnology have transformed not only the factory floor but also the way products are invented and designed, putting a premium on continual innovation and highly skilled workers. A shift in manufacturing toward smaller runs and custom-designed products is favoring agile and adaptable workplaces, business models, and employees, all of which have become a specialty in the United States. Future manufacturing will involve a global supply web, but the United States has a potentially great advantage because of our tight connections among innovations, design, and manufacturing and also our ability to integrate products and services. The National Academy of Engineering has been concerned about the issues surrounding manufacturing and is excited by the prospect of dramatic change. On June 11-12, 2012, it hosted a workshop in Washington, DC, to discuss the new world of manufacturing and how to position the United States to thrive in this world. The workshop steering committee focused on two particular goals. First, presenters and participants were to examine not just manufacturing but the broad array of activities that are inherently associated with manufacturing, including innovation and design. Second, the committee wanted to focus not just on making things but on making value, since value is the quality that will underlie high-paying jobs in America's future. Making Value: Integrating Manufacturing, Design, and Innovation to Thrive in the Changing Global Economy summarizes the workshop and the topics discussed by participants.

Lifelong Learning Imperative in Engineering: Sustaining American Competitiveness in the 21st Century - National Academy of Engineering (The National Academies Press, 2012)
The Lifelong Learning Imperative (LLI) project was initiated to assess current practices in lifelong learning for engineering professionals, reexamine the underlying assumptions behind those practices, and outline strategies for addressing unmet needs. The LLI project brought together leaders of U.S. industry, academia, government, and professional societies to assess the current state of lifelong learning of engineers; to examine the need for, and nature of, lifelong learning going forward; and to explore the responsibilities and potential actions for the primary stakeholders. The United States is facing a crisis in its engineering workforce just as global competition is becoming very intense. During the next several years there will be massive retirements of skilled and experiences engineers, and the United States has one of the lowest rates of graduation of bachelor-level engineers in the world: only 4.5 percent of our university graduates are engineers. The issue is especially acute in the national security industry because of citizenship requirements. Perhaps even more critical, the pace of technological change continues to accelerate, making the specifics of engineering education and skill development obsolete in short order. A critical part of our corporate and national strategy to address this looming crisis should be to ramp up the quality of engineers' professional life, improve their capacity to innovate, and widen their fields of opportunity. A project-framing workshop was organized by the University of Illinois at Urbana-Champaign (UIUC) in partnership with the National Academy of Engineering in June 2009 to examine the issues relevant to lifelong learning in engineering. A UIUC research team then conducted a survey-based assessment of the issues identified in the 2009 workshop. Preliminary findings from the UIUC study were examined more fully. Lifelong Learning Imperative in Engineering reflects the opinions of the authors based on the UIUS team's survey analysis and learning from the discussions at the 2011 workshop.

Lifelong Learning Imperative in Engineering: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2010)
The 21st century is witnessing a rapid increase in the pace of knowledge creation in the sciences and engineering. Competing in this global economy requires a science and engineering workforce that is consistently at the technological forefront. Dr. Charles Vest, President of the National Academy of Engineering, in a speech at the University of Michigan on October 15, 2007, put it simply: prospering in the knowledge age requires people with knowledge. The purpose of the Lifelong Learning Imperative Workshop, summarized in this volume, was to consider learning opportunities for the engineering professional. The participants in the workshop addressed the necessity of lifelong learning, the history of continuing education, possible delivery systems, systems used by other professions, and the current state of learning when viewed in the light of the rapid rate of technological change.

Information and Communication Technology and Peacebuilding: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2008)
Those who would use information and communication technology (ICT) in the cause of peace need to be cognizant of the risks as well as the benefits. ICT can facilitate positive dialogue but also hate speech. It can be used to fight corruption but also facilitate it. Simply giving people more information does not necessarily lead to predictable or positive results. As people become more informed, they may become more motivated to change their circumstances and to do so violently. On December 14, 2007, the National Academy of Engineering (NAE) convened a group of experts in diverse fields to consider the role of ICT in promoting peace and conflict resolution. The one-day workshop was designed to consider current and emerging technologies and strategies for employing them in conflict management and diplomacy. It also aimed to explore how organizations with a role in promoting peace, like the U.S. Institute of Peace, can most effectively leverage technology in carrying out their missions. Information and Communication Technology and Peacebuilding: Summary of a Workshop reviews the group's discussions on number of key issues, illuminates certain practitioner needs, and suggests possible next steps.

Research Briefings 1987 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
Each year since 1982 the Committee on Science, Engineering, and Public Policy has briefed the White House Office of Science and Technology Policy and the National Science Foundation on important progress in U.S. science and technology and major areas of research opportunity. This year the research briefing topics are \

Practical Guidance on Science and Engineering Ethics Education for Instructors and Administrators: Papers and Summary from a Workshop December 12, 2012 - National Academy of Engineering (The National Academies Press, 2013)
Over the last two decades, colleges and universities in the United States have significantly increased the formal ethics instruction they provide in science and engineering. Today, science and engineering programs socialize students into the values of scientists and engineers as well as their obligations in the conduct of scientific research and in the practice of engineering. Practical Guidance on Science and Engineering Ethics Education for Instructors and Administrators is the summary of a workshop convened in December 2012 to consider best practices for ethics education programs in science and engineering. The workshop focused on four key areas: goals and objectives for ethics instruction, instructional assessment, institutional and research cultures, and development of guidance checklists for instructors and administrators. Leading experts summarized and presented papers on current research knowledge in these areas. This report presents the edited papers and a summary of the discussions at the workshop.

Engineering for Pandemics: Preparedness, Response, and Recovery: Proceedings of a Forum - National Academy of Engineering
The 2020 Annual Meeting of the National Academy of Engineering took place under the most unusual circumstances in the Academy's 56-year history. In January 2020 the first few cases of a respiratory illness caused by a newly identified coronavirus were reported in the United States. By March, COVID-19 had become a global pandemic. As soon as the first few cases were reported, engineers began working wiith scientists, medical professionals, and others in the public and private sector to address needs generated by the pandemic. They brought automation, process control, and artificial intelligence to the production of protective equipment, diagnostics, and therapeutics. They established robust supply chains of critical materials. They strengthened the communication technologies and platforms that allowed people to telework and keep in touch with friends and family members. The 2020 annual meeting was held virtually. The two main plenary presentations, delivered by David Walt, the Hansj00f6rg Wyss Professor of Biologically Inspired Engineering at Harvard Medical School, and Pam Cheng, executive vice president of global operations and information technology for AstraZeneca, focused on the critical role of engineers in responding to the epidemic. Similarly, the annual forum, held the next day and organized by NAE executive officer Al Romig, Jr., and a distinguished organizing committee, was entitled \

Emerging Technologies and Ethical Issues in Engineering: Papers from a Workshop - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
Engineers and ethicists participated in a workshop to discuss the responsible development of new technologies. Presenters examined four areas of engineering2014sustainability, nanotechnology, neurotechnology, and energy2014in terms of the ethical issues they present to engineers in particular and society as a whole. Approaches to ethical issues include: analyzing the factual, conceptual, application, and moral aspects of an issue; evaluating the risks and responsibilities of a particular course of action; and using theories of ethics or codes of ethics developed by engineering societies as a basis for decision making. Ethics can be built into the education of engineering students and professionals, either as an aspect of courses already being taught or as a component of engineering projects to be examined along with research findings. Engineering practice workshops can also be effective, particularly when they include discussions with experienced engineers. This volume includes papers on all of these topics by experts in many fields. The consensus among workshop participants is that material on ethics should be an ongoing part of engineering education and engineering practice.

Harnessing Operational Systems Engineering to Support Peacebuilding: Report of a Workshop by the National Academy of Engineering and United States Institute of Peace Roundtable on Technology, Science, and Peacebuilding - National Academy of Engineering
Operational systems engineering is a methodology that identifies the important components of a complex system, analyzes the relationships among those components, and creates models of the system to explore its behavior and possible ways of changing that behavior. In this way it offers quantitative and qualitative techniques to support the design, analysis, and governance of systems of diverse scale and complexity for the delivery of products or services. Many peacebuilding interventions function essentially as the provision of services in response to demands elicited from societies in crisis. At its core, operational systems engineering attempts to understand and manage the supply of services and product in response to such demands. Harnessing Operational Systems Engineering to Support Peacebuilding is the summary of a workshop convened in November 2012 by the Roundtable on Science, Technology, and Peacebuilding of the National Academy of Engineering and the United States Institute of Peace to explore the question \

Frontiers of Engineering: Reports on Leading Edge Engineering from the 1996 NAE Symposium on Frontiers of Engineering - National Academy of Engineering
Space may have been called the \

Ethics Education and Scientific and Engineering Research: What's Been Learned? What Should Be Done? Summary of a Workshop - National Academy of Engineering
Increasing complexity and competitiveness in research environments, the prevalence of interdisciplinary and international involvement in research projects, and the close coupling of commerce and academia have created an ethically challenging environment for young scientists and engineers. For the past several decades, federal research agencies have supported projects to meet the need for mentoring and ethics training in graduate education in research, often called training in the responsible conduct of research. Recently, these agencies have supported projects to identify ethically problematic behaviors and assess the efficacy of ethics education in addressing them. With support from the National Science Foundation, the National Academy of Engineering Center for Engineering, Ethics, and Society held the workshop \

Overcoming Challenges to Infusing Ethics into the Development of Engineers: Proceedings of a Workshop - National Academy of Engineering (The National Academies Press, 2017)
On January 11201312, 2017, the National Academy of Engineering's Center for Engineering Ethics and Society (CEES) held a workshop designed to help the engineering community identify institutional and cultural challenges to instilling ethics in engineering programs and to develop approaches, programs, strategies, and collaborations to overcome those challenges. The workshop was a follow-on activity to the 2016 CEES report Infusing Ethics into the Development of Engineers: Exemplary Education Activities and Programs. This publication summarizes the presentations and discussions from the workshop.

Extraordinary Engineering Impacts on Society: Proceedings of a Symposium - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
On August 18-19, 2022, the National Academy of Engineering (NAE) held a symposium to explore how support of fundamental engineering and engineering education research by the National Science Foundation (NSF) has led to positive societal and economic impacts. The symposium - which was sponsored by the NSF Directorate for Engineering - was held to provide input to the NAE Committee on Extraordinary Engineering Impacts on Society as part of a larger effort to develop clear, compelling narratives for the public about the sources and effects of engineering innovations. Speakers at the symposium shared their personal stories and provided insights on how engineers influence not only technology and the national infrastructure but the economy, population health, manufacturing, disaster resilience, and many other aspects of daily life. This publication summarizes the presentations and discussion of the symposium.

Frontiers of Engineering: Reports on Leading Edge Engineering from the 1997 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1998)
Space may have been called the final frontier, but there are new frontiers to discover every day, and engineers are the ones exploring them. Through groundbreaking research and new technologies, engineers are able to go beyond traditional boundaries to do things that would have been all but impossible just a few years ago. This book, the most recent in a series of publications, describes new and emerging technologies and explains how they were developed and the benefits they will bring. It also offers highlights of the pioneering research and technological work being done by some of the country's emerging leaders in engineering. Topics include biomechanics, sensors and control for manufacturing processes, safety and security issues, decisionmaking tools for design and manufacturing, and intelligent transportation systems.

Using Data Sharing to Improve Coordination in Peacebuilding: Report of a Workshop by the National Academy of Engineering and United States Institute of Peace: Roundtable on Technology, Science, and Peacebuilding - National Academy of Engineering (The National Academies Press, 2012)
On May 23, 2012, the Roundtable on Technology, Science, and Peacebuilding convened a workshop at the United States Institute of Peace (USIP) to investigate data sharing as a means of improving coordination among US government and nongovernment stakeholders involved in peacebuilding and conflict management activities. Using Data Sharing to Improve Coordination in Peacebuilding:Report of a Workshop by the National Academy of Engineering and the United States Institute of Peace: Roundtable on Technology, Science, and Peacebuilding addresses the following question: What needs must a data sharing system address to create more effective coordination in conflict zones and to promote the participation of federal agencies and nonfederal organizations in Peacebuilding? In addition, the workshop served as a means to obtain feedback on the UNITY system, a data-sharing platform developed by the Department of Defense (DOD) and the United States Agency for International Development (USAID). The Roundtable was established in 2011 as a partnership between USIP and the National Academy of Engineering (NAE) to make a measurable and positive impact on conflict management, peacebuilding, and security capabilities by bringing together leaders from the technical and peacebuilding communities. Its members are senior executives and experts from leading governmental organizations, universities, corporations, and nongovernmental organizations. Its principal goals are: 1. To accelerate the application of science and technology to the process of peacebuilding and stabilization; 2. To promote systematic, high-level communication between peacebuilding and technical organizations on the problems faced and the technical capabilities required for successful peacebuilding; and 3. To collaborate in applying new science and technology to the most pressing challenges faced by local and international peacebuilders working in conflict zones. The Roundtable is strongly committed to action-oriented projects, and the long-term goal of each is to demonstrate viability with a successful field trial. The Roundtable has selected a portfolio of high-impact peacebuilding problems on which to focus its efforts: 1. Adapting agricultural extension services to peacebuilding, 2.Using data sharing to improve coordination in peacebuilding, 3. Sensing emerging conflicts, and 4. Harnessing systems methods for delivery of peacebuilding services.